Complete Nucleotide Sequence of an Escherichia coli Sequence Type 410 Strain Carrying bla(NDM-5) on an IncF Multidrug Resistance Plasmid and bla(OXA-181) on an IncX3 Plasmid - Overballe-Petersen, Søren (Genome Announc, 2018)
Using Nanopore sequencing, we describe here the circular genome of an Escherichia coli sequence type 410 (ST410) strain with five closed plasmids. A large 111-kb incompatibility group F (IncF) plasmid harbored bla(NDM-5) and 16 other resistance genes. A 51-kb IncX3 plasmid carried QnrS1 and bla(OXA-181). E. coli isolates with both bla(NDM-5) and bla(OXA-181) carbapenemases are rare.